Study on characteristics of sunscreen creams and body lotions containing various combinations of titanium dioxide and zinc oxide / Nur Sakinah Hasnan - Hasnan, Nur Sakinah (2013)
Sunscreen cream and lotion is one of agents that can protect skin from sun exposure. In this formulation of sunscreen cream and lotion, the Titanium dioxide (TiO2) and Zinc oxide (ZnO) are use as inorganic chemical agents that function as UV blocker. Objective of this research is to determine the characterization of sunscreen cream and lotion that containing various ratios of Titanium dioxide (TiO2) and Zinc oxide (ZnO). Characteristic that can be analyse are sun protection factor value, particle size, spreadability, viscoelasticity, zeta potential, firmness, cohesiveness and consistency of cream. The cream that show having good properties compare to others cream is cream of formulation 7 that contain Titanium dioxide (TiO2) 4.00gm, Zinc Oxide (ZnO) 2.00gm and olive oil 10gm. The lotion that show have the best properties compare to others lotion is lotion of formulation 14 that contain Titanium dioxide (TiO2) 6.00gm, Zinc Oxide (ZnO) 2.00gm and olive oil 20gm.